Kopi Anti-Diabetes “Mahoni Coffee” Untuk Pencegahan Penyakit Diabetes Melitus - Sisilia Teresia Rosmala Dewi; Rusdiaman Rusdiaman; Ismail Ibrahim; Sainal Edi Kamal (Jurusan Farmasi Politeknik Kesehatan Makassar, 2021)
Diabetes mellitus (DM) is one of the degenerative diseases that is now suffered by many people in the world, especially type 2 diabetes mellitus. can be used as an anti-diabetic drug. One of the plants commonly used as traditional medicine is the small leaf mahogany seed (Swietenia mahagoni Jacq.). Traditionally, the seeds are efficacious as a medicine for high blood pressure, diabetes, appetite stimulant, rheumatism medicine, fever, colds, gout, and eczema. The seeds of this mahogany contain high flavonoid compounds. The flavonoids that are also present in this coffee can give a pungent and bitter taste when consumed. Most people with diabetes are reluctant to eat mahogany seeds because of their bitter taste. Coffee, which is a favorite drink for most Indonesian people, can be an alternative to complementary functional drinks to cover the bitter taste of the mahogany seeds. We introduce to the posyandu cadres, Connect Java Village, Mamajang District, Makassar City, by practicing the way of making